FLUID INCLUSION STUDY ON GOLD DEPOSITS IN NORTHWESTERN ERGUNA METALLOGENIC BELT, CHINA - Wu G.; Sun F.Y.; Ding Q.F.; Wang L.; Zhao C.S. (My University, 2007)
A lot of gold deposits and occurrences, including the Shabaosi, Laogou and Xiaoyinuogaigou deposits, have been recently found in northwestern Erguna metallogenic belt along the southeastern margin of the Mongol-Okhotsk Orogen, which is an important Ag-Pb-Zn-Mo-polymetal metallogenic belt in Northeast China. These Au deposits are strictly controlled by two ductile shear zones, i. e. the E-W-trending Luoguhe-Ergenhe and NNE-trending Ergunahe ductile shear zones. Orebodies are hosted in subsidiary fractures of these two ductile shear zones. Ores of these gold deposits contain ≤3% of sulphides dominated by pyrite. Fluid inclusions in quartz crystals can be classified into aqueous two-phase, CO2-bearing three-phase and pure CO2 types. The bubbles (vapor-phase) are mainly composed of H2O, CO2 and N2, with minor of H2S, CH4. The salinities range from 2.06% to 8.54% NaCl eqv. Homogenization temperatures for the Laogou and the Xiaoyinuogaigou gold deposits range from 171°C to 452°C, 169°C to 493°C, respectively, suggesting that both deposits are mesothermal. The ore-forming pressures of the Laogou and the Xiaoyinuogaigou deposits are 61 - 122MPa with average of 82MPa and 38 - 172MPa with average of 93MPa, corresponding to depths of 6 - 9km and 4 - 11km, with averages of 7km and 8km, respectively. The pressure fluctuations may be due to faulting. Hence the geological and geochemical features of the deposits are similar to those of orogenic gold deposits worldwide. The origin of these gold deposits may be related to Mesozoic collisional orogeny between the Siberia and Mongolia-Sinokorea continents.
Keywords: ERGUNA METALLOGENIC BELT; FLUID INCLUSION; MONGOL-OKHOTSK OROGEN; NE CHINA; OROGENIC GOLD DEPOSIT